Short physical performance battery as a practical tool to assess mortality risk in chronic obstructive pulmonary disease - Fermont, Jilles M; Mohan, Divya; Fisk, Marie; Bolton, Charlotte E; Macnee, William; Cockcroft, John R; McEniery, Carmel; Fuld, Jonathan; Cheriyan, Joseph; Tal-Singer, Ruth; Müllerova, Hana; Wood, Angela M; et al. (Age and ageing, 2021)
Abstract Rationale chronic obstructive pulmonary disease (COPD) is a leading cause of mortality and common in older adults. The BODE Index is the most recognised mortality risk score in COPD but includes a 6-minute walk test (6MWT) that is seldom available in practise; the BODE Index may be better adopted if the 6MWT was replaced. Objectives we investigated whether a modified BODE Index in which 6MWT was replaced by an alternative measure of physical capacity, specifically the short physical performance battery (SPPB) or components, retained its predictive ability for mortality in individuals with COPD. Methods we analysed 630 COPD patients from the ERICA cohort study for whom UK Office for National Statistics verified mortality data were available. Variables tested at baseline included spirometry, 6MWT, SPPB and its components (4-m gait speed test [4MGS], chair stand and balance). Predictive models were developed using stratified multivariable Cox regression, and assessed by C-indices and calibration plots with 10-fold cross-validation and replication. Results during median 2 years of follow-up, 60 (10%) individuals died. There was no significant difference between the discriminative ability of BODE6MWT (C-index 0.709, 95% confidence interval [CI], 0.680–0.737), BODESPPB (C-index 0.683, 95% CI, 0.647–0.712), BODE4MGS (C-index 0.676, 95% CI, 0.643–0.700) and BODEBALANCE (C-index 0.686, 95% CI, 0.651–0.713) for predicting mortality. Conclusions the SPPB, and its 4MGS and balance components, can potentially be used as an alternative to the 6MWT in the BODE Index without significant loss of predictive ability in all-cause mortality.